Escolas rurais de morada nova/ceará e o uso das Tecnologias Digitais da Informação e Comunicação (TDIC) - Sousa, katiane Almeida de (Universidade Federal Rural do Semi-Árido, 2018)
Currently, we live in a network society, in a social organization model classified by many as cyberculture (Lévy, 1999), where the technology and information spread at immeasurable speed. However, these evolution doesn't get to all the parts, let alone all of the subjects, that's why we can talk about technological and social exclusion, especially when we take as reference the rural locations that historically suffer from the lack of public policies. The school, as a primordial space to the formation of citizens, becomes the analysis point of this research, so we can realize up to which extent the rural schools are digitally included by public policies and how the subjects that act on this space behave in relation to the technological inclusion/exclusion they live. For this reason, our research goal is: analyze the working conditions with TDIC in the rural public schools of Morada Nova - Ceará, contemplating the public policies, structural conditions and teacher qualification. To fulfill the purpose above mentioned, we performed a qualitative research with field research in the selected schools, where we used as methodology the application of structured interviews with the teachers of the municipal public network of Morada Nova – CE, that act on the rural zone, and carried out questionnaires with six managers of the respective schools. The first methodological procedure was made to investigate about the teacher qualification of those who teach at the rural zone to use it on the TDIC and about the teaching practices involving technologies and the expectations about formation and difficulties encountered. The surveys were applied to directors to map the technological resources available at the schools and how they are used. As results, although many schools have computing laboratories, computers, and other resources to some extent, the structure for a broadband network to support the usage of the laboratories' computers is missing and we also noticed the lack of active public policies in the schools to make use of TDIC. With respect to teacher formation, it was shown as insufficient to the teachers and the broadband network used to plan their pedagogical activities and execute differentiated teaching practices to use with the TDIC was also missing. Thereby, we conclude that the governmental actions linked to the usage of TDIC on rural schools are still lacking, missing the structure and continuous training that meet the desires of the teachers towards the realization of teaching practices with the usage of TDIC in the classroom
Keywords: Inclusão digital; Escola Rural; Ensino; Formação de Professor; Políticas públicas; Digital Inclusion; Rural School; Teaching; Teacher formation; Public policies; MULTIDISCIPLINAR::ENSINO